Stereotypical Representation of Women in the Film Polite Society - Alif Arya Fernanda; Fajar Junaedi (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − This study aims to analyze the stereotypical representation of women in the film Polite Society through Roland Barthes' semiotic approach by examining eight scenes that demonstrate gender construction through denotative, connotative, and mythical signs. Method − This study employs a qualitative descriptive approach. Descriptive analysis aims to systematically and comprehensively present data, facts, and phenomena. The analysis specifically focuses on scenes that depict stereotypes of women. The data consist of screenshots from selected scenes as well as excerpts of dialogue, which are used to interpret the meanings conveyed in each scene. Findings − The results of the study show that the film represents various stereotypes that limit women, such as the assumption that they are not suitable for working in risky fields, are considered emotional, must obey the family structure, and make marriage the main achievement. Through language, gestures, social relationships, and family dynamics, the film shows how patriarchal values ​​work subtly and are normalized. These findings confirm that Polite Society not only provides entertainment, but also builds a critical discourse about the limitations of women in popular culture.